ANALISIS KARAKTER SOSIAL MELALUI PERMAINAN DAKON - Halimatussadiah Halimatussadiah (EJoES (Educational Journal of Elementary School), 2020)
This study aims to analysis of social character through dakon game. Subjects consisted of 16 students from Medan Perwanis Kindergarten. The problem formulation is how can the game of dakon foster the social character of students and what social characters are produced from the dakon game? Where as the purpose is to describe how dakon games can foster students' social character and describe what social characters are produced from dakon games. By using descriptive qualitative research methods, with observation and documentation data collection techniques, it was found that social characters formed for Medan Perwanis Kindergarten students through dakon games, among others: honest character, tolerance, discipline, creative, communicative, peaceloving, and responsibility